2009
DOI: 10.1158/1078-0432.ccr-09-0110
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation Combined with KS-IL2 Immunocytokine (EMD 273066) Results in an Enhanced Antitumor Effect against Murine Colon Adenocarcinoma

Abstract: Purpose: Radiofrequency ablation (RFA) is a common treatment modality for surgically unresectable tumors. However, there is a high rate of both local and systemic recurrence. Experimental Design: In this preclinical study, we sought to enhance the antitumor effect of RFA by combining it with huKS-IL2 immunocytokine [tumor-specific monoclonal antibody fused to interleukin-2 (IL2)] in mice bearing CT26-KS colon adenocarcinoma. Mice were treated with RFA, huKS-IL2 via intratumoral injection, or combination therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 48 publications
0
35
0
Order By: Relevance
“…Besides PD-L1 and PD-1, CTLA-4 has been shown to inhibit thermal ablation-induced antitumor activities (4, 30, 31). Besides immune inhibitory pathways, it has been shown that various cytokines that are used to enhance T cell homeostasis and T cell immune responses also increase the antitumor efficacy of RFA (32, 33). Thus future combination therapy with RFA and various immune modulators can be explored in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Besides PD-L1 and PD-1, CTLA-4 has been shown to inhibit thermal ablation-induced antitumor activities (4, 30, 31). Besides immune inhibitory pathways, it has been shown that various cytokines that are used to enhance T cell homeostasis and T cell immune responses also increase the antitumor efficacy of RFA (32, 33). Thus future combination therapy with RFA and various immune modulators can be explored in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…This was confirmed in the clinical setting where both cell types were upregulated in the peripheral blood of patients as a result of L19-IL2 treatment (34). Johnson and colleagues (45) combined an alternative immunocytokine, KS-IL2, with radiofrequency ablation in a murine colon adenocarcinoma (CT26). The combination increased growth suppression, and a greater proportion of CD4 þ and CD8 þ cells was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Ex vivo interferon (IFN) response assays were conducted as previously described (26). Splenocytes from B78 tumor-bearing animals were harvested on day 12 of indicated treatment and co-cultured with B16 cells for 5 days.…”
Section: Methodsmentioning
confidence: 99%